(untitled) (Vietnam Journal of Community Medicine, 2022)
A cross-sectional study was conducted on 421 patients with type 2 diabetes from ≥ 20 years old at Ha Nam Provincial General Hospital. Objective: Describe nutritional status and some related factors. Method: Cross-sectional description. Results: According to the classification of the World Health Organization Office for the Western Pacific (WPRO), the results showed that the percentage of study subjects with normal BMI was 46.8%; overweight and obesity was 53.2%. The prevalence of overweight and obesity in men was 56.3% higher than that of women 49.7%. Some factors related to overweight and obesity have statistical significance (p < 0.05): The high waist/hip ratio group has risk of obesity 2.55 times higher (95% CI: 1.08 - 6) than that of the normal waist/hip group. The economic well-off/rich group has higher risk of obesity 3.04 times (95%CI: 2.04 – 4.55) than the poor/medium economic group.